ENHANCING STUDENTS' CRITICAL THINKING IN NUMERACY PROBLEM-SOLVING THROUGH A FIELD-INDEPENDENT LEARNING STYLE AND HIGH SELF EFFICACY - Yustitia, Via; Murti, Varissa Sarahma; Kusmaharti, Dian; Faridah, Luluk (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
The urgency of addressing the lack of critical thinking skills among class V-B students at elementary school Ketintang 1 Surabaya is paramount. This study aims to elucidate the critical thinking abilities of students who exhibit a field-dependent cognitive style and high self-efficacy. The study employed a qualitative approach and phenomenological method. Data collection involved the use of the Group Embedded Figures Test (GEFT), self-efficacy questionnaires, and critical thinking assessments in mathematics, specifically on topics related to cubes and rectangular prisms. Data analysis comprised data condensation, data presentation, and conclusion drawing. Based on GEFT and self-efficacy questionnaire results, one class V-B student with a field-dependent cognitive style and high self-efficacy was selected for further critical thinking skills assessment. Based on the results of the critical thinking skills test, the student with a field-dependent cognitive style and high self-efficacy demonstrated notable strengths. In the process of basic clarification, the student met the indicators for analyzing arguments and formulating statements, effectively presenting their arguments. When providing reasons for decisions, the student showed the ability to consider the credibility of sources by selecting appropriate problem-solving strategies. However, she occasionally made calculation errors due to inaccuracy. In the process of concluding, the student met the indicators for making and evaluating decisions, successfully composing conclusion sentences that aligned with the problems and final answers.